HARMONIZATION OF TEACHER EDUCATION - Gennady I. Sarantsev (Moscow Polytechnic University, 2016)
The article examines the contents of the key concepts of bachelor's degree in teacher education, such as fundamentalization, practical orientation, harmonization. As a means of harmonization of the fundamental nature and the practical orientation of vocational education methodical thinking is considered. Methodical thinking enables teacher to conduct research, to carry out experiments, to describe their results, to apply different approaches and conceptions, to implement multiple professional methods, and to become a competent participant of a pedagogical community. Methodical thinking being a key competence of a Bachelor ties fundamentalization together with practical orientation.